Exploration and refinement of migratory routes in long-lived birds - Fayet, AL (Wiley, 2020)
How migration routes develop in long-lived migratory animals remains poorly understood. Campioni et al. (2019) tracked the migration of immature and breeding Cory’s shearwaters and found that the timings and routes gradually changed with age. Young birds followed more exploratory routes at first, but gradually shortened and defined them as they matured, and they returned to the breeding grounds progressively earlier. These findings suggest that long-lived species start by exploring potentially suitable areas for the non-breeding season and progressively refine their migration route as they age.